Pharmaceutico-Analytical Study of Naga Bhasma by Using Rasatarangini Reference (International Journal of Ayurveda and Pharma Research, 2023)
Naga bhasma is one of the herbo-metallic preparations used in Ayurveda. In this study an effort has been made to establish standards for Naga bhasma prepared by using classical ref. described in Rasatarangini with classical format, Shodhana, Jarana, Bhavana & Marana. In Samanya & Vishesha ‘Shodhana’ (purification process) removes heavy metals other than lead, apart from making it soft and acquiescent for trituration. Jarana process is pre-procedure of Marana for all Puti loha. For putapka of Putiloha without Jarana process it difficult to convert the Bhasma because these metal have low melting point. Manahshila is Ariloha of Naga. Ariloha is used as Maraka Dravya for preparation of Bhasma which acts as supporting agent to help the efficacy of Bhasma. Black coloured Naga Bhasma was obtained after 10 Puta by using classical Puta. Prepared Naga bhasma subjected to tests mentioned in Ayurvedic texts Varitar, Rekhapurnatva, & Unnam, tests and physico-chemical analysis such as pH Value, Total Ash, Loss on drying and acid insoluble ash.